1996
DOI: 10.1093/nar/24.3.418
|View full text |Cite
|
Sign up to set email alerts
|

Novel Activities of Human Uracil DNA N-Glycosylase for Cytosine-Derived Products of Oxidative DNA Damage

Abstract: Uracil DNA N-glycosylase is a repair enzyme that releases uracil from DNA. A major function of this enzyme is presumably to protect the genome from pre-mutagenic uracil resulting from deamination of cytosine in DNA. Here, we report that human uracil DNA N-glycosylase also recognizes three uracil derivatives that are generated as major products of cytosine in DNA by hydroxyl radical attack or other oxidative processes. DNA substrates were prepared by gamma-irradiation of DNA in aerated aqueous solution and incu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 25 publications
3
61
0
Order By: Relevance
“…There is, however, sufficient space to allow small substituents such as hydroxy or carbonyl groups at the 5-or 6-positions. Thus certain uracil analogues generated from cytosine by γ-irradiation are recognized by UDG, but are excised at considerably lower rates than uracil [27,29]. This steric shielding has been verified by sitespecific mutagenesis of Tyr"%( of human UDG to Ala [82], which results in a mutant that excises thymine as well as uracil from DNA ( Figure 6).…”
Section: Figure 5 Udg-dna Interactionsmentioning
confidence: 85%
See 1 more Smart Citation
“…There is, however, sufficient space to allow small substituents such as hydroxy or carbonyl groups at the 5-or 6-positions. Thus certain uracil analogues generated from cytosine by γ-irradiation are recognized by UDG, but are excised at considerably lower rates than uracil [27,29]. This steric shielding has been verified by sitespecific mutagenesis of Tyr"%( of human UDG to Ala [82], which results in a mutant that excises thymine as well as uracil from DNA ( Figure 6).…”
Section: Figure 5 Udg-dna Interactionsmentioning
confidence: 85%
“…These include 5-fluorouracil in DNA found after treatment with 5-fluorouracil [26], as well as isodialuric acid, 5-hydroxyuracil and alloxan, which are all formed from cytosine in DNA after exposure to γ-irradiation or oxidative stress [27][28][29]. Uracil at the 3h-end of a DNA chain is not removed by human [30] or E. coli [31] UDGs, whereas uracil at the 5h-end is removed provided that it is phosphorylated.…”
Section: Udgsmentioning
confidence: 99%
“…Surprisingly, while 5-OHU is the preferred substrate of NEIL2, three other human enzymes, namely NEIL1, NTH1, and uracil-DNA glycosylase, are also able to excise this lesion from DNA (10,23,24). This raises the possibility that 5-OHU, an important mutagenic lesion generated in significant amount in the genome, requires several back-up enzymes for its repair.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, the activity and expression of NTH1 and OGG1 were found to be significantly altered during the acute (16-18 weeks) and early chronic (24 weeks) phases of hepatitis in the Long Evans Cinnamon (LEC) rat, an animal model for Wilson's disease (WD) which is said to cause a "genetically induced" oxidative condition and higher risk for liver cancer [89]. Several studies indicated that SMUG1 and UNG1 are also capable of excising oxidized derivatives of pyrimidines and siRNA-mediated downregulation of these genes in mouse embryo fibroblasts significantly increased radio sensitivity [91,92]. In view of the presence of multiple DNA glycosylases further studies are required before we could evaluate their contribution to normal cellular functions.…”
Section: Redundancy Of Ber Enzymes: Distinctive Biological Rolesmentioning
confidence: 99%